Weton Calculations as A Basis for Marriage Implementation (Case Study at Kandangmas Dawe Kudus) - Nafi', Muhamad Agus Yusrun (Jurnal Penelitian, 2023)
This research uses a qualitative method with an Islamic Law approach which examines basic norms, implementation of basic norms, and the impact of basic norms in calculating marriage weton at Kandangmas Dawe Kudus.. Research purposes This is to describe Many people do the calculation of weton in marriages in the Kandangmas Dawe Kudus community, but researchers also found people who don’t believe or ignore the calculation of weton births in marriage, this is motivated by family, community environment, strong religious beliefs and belief in qadha and qadar. Research result: The people of Kandangmas Dawe Kudus need a wise and wise attitude to pay attention to old values   or traditions such as good weton calculations and accept new values   that are better and more useful so that they remain in line with the times and the values of noble Islamic teachings. As long as it does not change the faith and contradict the teachings of Islam, such traditions can be implemented and developed. On the other hand, if it conflicts with the teachings of the Islamic religion, then the tradition must be abandoned.